Advances and challenges in the transsexualizing process in the Brazilian Unified Health System - Boldrin, Vitória da Cruz; Coelho, Ruan Dias Rodrigues; Alves, Letícia Carvalho; Teixeira, Edenilson de Souza; Bernardo, Sheila Reis de Souza; Costa, Anacely Guimarães [UNESP] (FapUNIFESP (SciELO), 2025)
The implementation of the Transsexualizing Process (TP) / Gender-affirming Surgeries (GAS) in the Unified Health System (SUS) was the result of social struggles by the LGBT community for sexual rights, the construction of gender identity, and bodily autonomy. The scope of this article is to analyze the advances and challenges of TP/GAS in the SUS, through a qualitative narrative literature review. In June 2022, searches were conducted in the Google Scholar, SciELO, and VHL databases to select scientific articles in Portuguese published in the last 10 years, excluding articles in foreign languages and other types of academic work such as reviews, undergraduate theses, dissertations, and/or graduate theses. Eighteen articles were selected that showed the expansion of healthcare services for transsexuals with GAS in the SUS. However, weaknesses were identified, such as unprepared healthcare professionals, social stigmas, clinical diagnosis as a driver of pathologization, and low hospital coverage. The regulation and availability of GAS in the SUS have brought gains to the trans population, but it is necessary to expand access to services and mitigate stigmatizing conduct to ensure that these individuals feel accepted in their entire biopsychosocial context.
Avances y desafíos en el proceso de transexualización en el Sistema Único de Salud brasileño
Avanços e desafios no processo transexualizador no Sistema Único de Saúde brasileiro
Keywords: Gender; Health technologies; Public health policies; Transsexuality